(untitled) (World Bulletin of Public Health, 2024)
Colorectal cancer is one of the most common cancers in the world. In the Russian Federation, about 40 thousand new cases of the disease are registered annually. Five-year survival rate for rectal cancer depends on the stage of the disease and ranges from 50% for stage I to 20% for stage IV. Currently, combined treatment with radiation therapy is the standard of care for resectable rectal cancer. Radiation therapy can reduce the size of the tumor, which facilitates surgery, and reduces the risk of local recurrence of the disease.